2021
DOI: 10.3389/fphar.2021.649398
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Chaer Prevents Cardiomyocyte Apoptosis From Acute Myocardial Infarction Through AMPK Activation

Abstract: Long non-coding RNA (lncRNA) is widely reported to be involved in cardiac (patho)physiology. Acute myocardial infarction, in which cardiomyocyte apoptosis plays an important role, is a life-threatening disease. Here, we report the lncRNA Chaer that is anti-apoptotic in cardiomyocytes during Acute myocardial infarction. Importantly, lncRNA Chaer is significantly downregulated in both oxygen-glucose deprivation (oxygen-glucose deprivation)-treated cardiomyocytes in vitro and AMI heart. In vitro, overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…lncRNA Chaer was significantly down-regulated in hypoxia-treated cardiomyocytes and in the hearts of myocardial infarction [35]. In vitro overexpression of lncRNA Chaer reduced hypoxia-induced cardiomyocyte apoptosis; conversely, silencing of lncRNA Chaer promoted cardiomyocyte apoptosis [35]. In vivo overexpression of lncRNA Chaer slowed myocyte apoptosis, reduced the infarcted area, and improved cardiac function in infarcted mice, suggesting that lncRNA Chaer has a protective effect against myocardial infarction [35].…”
Section: Ncrnas and Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…lncRNA Chaer was significantly down-regulated in hypoxia-treated cardiomyocytes and in the hearts of myocardial infarction [35]. In vitro overexpression of lncRNA Chaer reduced hypoxia-induced cardiomyocyte apoptosis; conversely, silencing of lncRNA Chaer promoted cardiomyocyte apoptosis [35]. In vivo overexpression of lncRNA Chaer slowed myocyte apoptosis, reduced the infarcted area, and improved cardiac function in infarcted mice, suggesting that lncRNA Chaer has a protective effect against myocardial infarction [35].…”
Section: Ncrnas and Cardiovascular Diseasesmentioning
confidence: 99%
“…In vitro overexpression of lncRNA Chaer reduced hypoxia-induced cardiomyocyte apoptosis; conversely, silencing of lncRNA Chaer promoted cardiomyocyte apoptosis [35]. In vivo overexpression of lncRNA Chaer slowed myocyte apoptosis, reduced the infarcted area, and improved cardiac function in infarcted mice, suggesting that lncRNA Chaer has a protective effect against myocardial infarction [35]. lncRNA Nron expression was elevated in the peripheral blood of myocardial infarcted patients and in hypoxia-stimulated H9c2 cells [36].…”
Section: Ncrnas and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaer -PRC2 interaction is transiently promoted by the mammalian target of rapamycin (mTOR) pathway upon stress or hormonal stimuli and ultimately results in the induction of the genes responsible for heart hypertrophy ( Wang et al, 2016 ). Moreover, a recent work showed that Chaer is significantly downregulated in cardiomyocytes of a murine acute myocardial infarction model and that its overexpression, both in vitro and in vivo , reduces cardiomyocyte apoptosis and heart function impairment through a mechanism dependent on AMP-activated protein kinase (AMPK) phosphorylation ( He et al, 2021 ). Several other lncRNAs have been associated with cardiac mesoderm development, including Braveheart ( Bvht ) and cardiac mesoderm enhancer-associated non-coding RNA ( CARMEN ).…”
Section: Rna-mediated Epigenome Regulationmentioning
confidence: 99%
“…For instance, Wu et al found that bradykinin (BK) could reduce myocardial apoptosis by reducing caspase-3 expression in a human cardiac c-Kit + progenitor cell (hCPCs) myocardial infarction model, thereby improving ischemic heart disease (Wu et al, 2021a), Uberti F et al showed that levosimendan could interfere with mitochondrial function by regulating mitoK (ATP) channels and NO, and could control the interaction between autophagy and apoptosis to protect H9c2 cells against oxidative damage (Uberti et al, 2011), Nie et al reported that lncRNA AK006774 could reduce I/R-induced infarct size and myocardial apoptosis by regulating Bcl-2 expression through miR-448 in a mouse I/R model (Nie et al, 2021), Xu et al found that GSK-3β upregulated CD47 expression in cardiac tissues after MI by activating NF-κb, and then regulated apoptosis leading to myocardial injury (Xu et al, 2021). Besides, AKT1/GSK3β, NF-κb, and other related signaling molecules can also regulate apoptosis in cardiovascular diseases (Supplementary Table S1) (Shen et al, 2020;Jiang et al, 2021a;Wang et al, 2021a;Jiang et al, 2021b;He et al, 2021;Lu et al, 2021;Sun et al, 2021;Xiong et al, 2021;Xu et al, 2021).…”
Section: Different Types Of Pcd and Molecular Mechanisms In Cardiovascular Diseases Apoptosis Pathways In Cardiovascular Diseasesmentioning
confidence: 99%